Titanium-released from dental implant enhances pre-osteoblast adhesion by ROS modulating crucial intracellular pathways - Rossi, M. C. [UNESP]; Bezerra, F. J.B. [UNESP]; Silva, R. A. [UNESP]; Crulhas, B. P. [UNESP]; Fernandes, C. J.C. [UNESP]; Nascimento, A. S. [UNESP]; Pedrosa, V. A. [UNESP]; Padilha, P. [UNESP]; Zambuzzi, W. F. [UNESP] (Wiley, 2017)
It is important to understand the cellular and molecular events that occur at the cell–material interface of implants used for bone repair. The mechanisms involved in the initial stages of osteoblast interactions with the surface of the implant material must be decisive for cell fating surrounding them. In order to address this issue, we decided to investigate if conditioned medium for dental implants was able to modulate murine pre-osteoblast metabolism. First, we determined the concentration of titanium (Ti)-containing conditioned medium and found that it was 2-fold increased (p < 0.0001). We have reported that this conditioned medium significantly up-modulated pre-osteoblast adhesion up to 24 h (p < 0.0001). In parallel, our results showed that both phosphorylations of FAK (focal adhesion kinase) at Y397 (p < 0.0011) and Cofilin at Ser03 (p < 0.0053) were also up-modulated, as well as for Rac1 expression (p < 0.0175); both of them are involved with cell adaptation by rearranging cytoskeleton actin filaments. Thereafter, Ti-containing medium stimulated ROS (reactive oxygen species) production by pre-osteoblast cells, and it is very possible that ROS compromised PTP-1B (protein tyrosine phosphatase 1B) activation since PTP1B was down-phosphorylated (p < 0.0148). The low PTP activity guarantees the phosphorylation of FAK at Y-residue, causing better pre-osteoblast adhesion in response to Ti-containing medium. Altogether, these data indicate that ROS indirectly modulate FAK phosphorylation in response to Ti-released from dental implants. Taken the results in account, these data showed for the first time that the implanted dental device is able to dynamically affect surrounding tissues, mainly by promoting a better performance of the pre-osteoblast cells. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 2968–2976, 2017.
Keywords: cell adhesion; dental implants; pre-osteoblast; signal transduction; titanium